Peranan Pengambil Kebijakan dalam Pengembangan Masyarakat - M. Hubeis (Jurnal Komunikasi Pembangunan, 2010)
System of government in Indonesia that has been changed from centralized (top-down) to decentralized (bottom-up)or autonomous regions (Regional Autonomy) is marked based on the Law No. 22/1999 on Regional Government,which was revised by Law No. 32/2004 and supported by Law No. 25/2004 (a combination of top-down and bottomupapproaches). In this case, policy makers as professionals have an important role in the development effectively,namely the Supervision and Control. Policy regarding institutional arrangements (policy level) and the limits ofautonomy in collective decision-making process in accordance with the strata in Indonesia, according to the policylevel, the title and its implementation, involves a variety of development actors (ABG-C: Academician, Business,Government and Community). Policies in community development is the crystallization of the design communityneeds that cannot be separated from the matters that empower and restrict it from the pressures ofideological/cultural and structural, as well as active involvement of communities in the process of day-to-day policy.